Relapse in melioidosis: incidence and risk factors. - Chaowagul, W; Suputtamongkol, Y; Dance, D; Rajchanuvong, A; Pattara-arechachai, J; White, N (1993)
From 1986 to 1991, 602 patients with melioidosis were seen in Sappasitprasong Hospital, Ubon Ratchatani, Thailand. The in-hospital mortality was 42%. Of 118 adult patients followed long-term, 27 (23%) had culture-proven relapses of melioidosis (3 relapsed twice), a relapse rate of 15% (95% confidence interval [CI], 11-22) per year. The median time from discharge to relapse was 21 weeks (range, 1-290). In 44% of patients, relapses included septicemia, and 27% died. Patients with severe disease (multiple foci of infection or septicemia) relapsed 4.7 times (95% CI, 1.6-14.1) more frequently than patients with localized melioidosis. Underlying disease was not a risk factor, but initial parenteral treatment with ceftazidime reduced the risk of relapse 2-fold (95% CI, 1.1-3.4). Relapses were 3.3 (95% CI, 1.4-9.0) times more frequent following short-course (< or = 8 weeks) oral coamoxiclav than after the oral combination regimen of chloramphenicol, doxycycline, and cotrimoxazole. Longer oral treatment with either reduced relapse 1.6-fold (95% CI, 1.2-1.9). The optimum choice and duration of antibiotic treatment to prevent relapse in melioidosis remain to be determined.